Factors affecting customer loyalty for mobile phone users of Sarawak's public agencies / Al-Nadzirul Mubin Arbi and Mohd Faidzul Firdaus Sukaimi - Arbi, Al-Nadzirul Mubin; Sukaimi, Mohd Faidzul Firdaus (University Technology MARA Sarawak, 2016)
In our modern world nowadays, society starts of their lives peeking through their mobile phones. To get the latest news and updates of their surroundings they need to have an efficient mobile phones where the battery is reliable, built quality is superb and an affordable price. These factors are some of the reasons why people actually prefer their smartphone or mobile phone brands to the others. Some might say that people have their personal biasness over certain brands due to the longevity of their loyalty to certain brands even though the brand sometimes produces incompetent quality compared to other brands. This is where we study customer loyalty factors towards their mobile phone or smartphone particularly in public agencies. The research will be conducted in State Human Resource Unit in Kuching and P.218 Sibuti Parliamentary Office in Miri where the subjects will be the employees there. The research that will be conducted in a team of two at different public agencies simultaneously will enable us to see what actually the factors that causing their loyalty to such brands. The factors that will be tested are the service quality that the mobile phone company gives to their customers, brand image of the mobile phones and the purchasing power of the public agency's employees in buying their mobile phones. This study also will look at the perceptions of loyalty between male and female in the chosen public agencies. By looking at the factors, we will also can measure the level of 1 satisfaction for the factors in buying mobile phones for the chosen public agencies.